Development of ARM based embedded controller for mass flow controller system - Iyer, N.; Shinde, S.; Dhawale, T.; Shelar, N. (9th International Conference on Trends in Industrial Measurement and Automation, TIMA 2017., 2017)
The purpose for this paper is to describe the central Embedded Controller development done for Mass Flow Controllers (MFCs) M100B system. Work caters to control M100B MFCs being used for one of the systems at National Chemical Laboratory. M100B MFC accurately measures and controls the mass flow rates of gases. The central controller for this system is non functional and technology is outdated and hence new central embedded controller is developed for the system. Development is done using ARM7 32-bit RISC microcontroller Philips LPC2148, as low power and high frequency design. Serial ADCs are interfaced to ARM microcontroller. LCD display 20×4 is used for display of run status, diagnostic and error messages. Touch keypad is designed and interfaced for setting of mass flow rate for different MFCs against MFC number selected by keypad. The software development is done using Keil micro vision 4. This ARM based controller is a real time system with display of diagnostic and error messages.